Everything I know about success I learned from Napoleon Hill : essential lessons for using the power of positive thinking - Green, Don (McGraw Hill-Ascent Audio, 2022)
Napoleon Hill's landmark Think and Grow Rich remains one of the biggest bestsellers of all time, with over twenty million copies in print and translated into more than thirty languages. Hill's philosophy of personal achievement, wealth, and empowerment created millionaires the world over. Are you ready to put the power of Napoleon Hill to work for you? In this new book, the Napoleon Hill Foundation's own executive director puts Hill's essential principles right at your fingertips. Filled with fascinating stories from Dolly Parton, Jeffrey Gitomer, Chief Poly Emenike, and Joe Dudley, Jr.-iconic figures who each applied Hill's principles to their own lives-Everything I Know About Success I Learned from Napoleon Hill lays out the tools needed to uncover the secrets of growth, creativity, power, and achievement inside all of us. It's an essential playbook for any business professional seeking the knowledge and inspiration necessary to discard fear and attain the goals of personal and professional triumph. The author also details Napoleon Hill's influence on his own success, growing up in rural Virginia and moving on to become a bank CEO at just forty-one years old.